Influencia del nivel socioeconómico en las actitudes frente a problemas de salud bucodental en adultos de 35 años en la ciudad de Latacunga - Cevallos Cáceres, María Paula (2025)
Introduction: Oral and oral pathologies afflict almost half of the population of the world. However, economically and socially disadvantaged populations are unfairly affected to a greater extent. In other words, a relationship between socioeconomic status, attitudes and perceptions about oral health could be established. Objective: To establish the relationship between socioeconomic status and attitudes towards oral health problems. Materials and methods: An observational, cross - sectional, retrospective and descriptive study was carried out. A survey was administered to a sample of 384 individuals to collect information on socioeconomic level and attitudes towards dental health problems. These variables were subsequently analyzed in a cross - sectional manner with a chi2 test. Results: The results of the chi2 test fall in the rejection zone, where the alternative hypothesis is accepted and the null hypothesis is rejected, so it can be affirmed that socioeconomic level has an impact on attitudes towards dental pain. Conclusions: There is a close relationship between the socio - economic level of people and the attitudes that are assumed through the actions executed in the face of oral health problems. The economic gap, the limited access to health services, the high costs of preventive and corrective treatments, mainly of a cultural nature, are important factors in the progression of oral diseases.